Portability and flexibility of physiotherapy tools for rehabilitation of people with obesity - Abdul Rahman, Julaila; Zabidi, Nur Shahirah Nabilah; Kamaruddin, Zumahiran; Awang, Arita Hanim (2017)
The obesity rate in Malaysia is kept on increasing year by year. The causes for this issue are including unhealthy food intake and unhealthy lifestyle. As the obesity issues in Malaysia worsen, it leads to other problem such as diabetes, heart attack, stroke and also others physical problem. One of it is concerning on physical condition of the ankle. The ankle is the most important parts of a human structure that will affect human body posture. This means that activities were done are heavily influence by ankle condition leads to inefficiency of job performance. Physiotherapy tools are important for the rehabilitation process. The rehabilitation process is known as a healing process, which is essential in ensuring the improvement of health and physical condition of a patient, especially with obesity. Physiotherapist treatment is essential to ensure the effectiveness of rehabilitation process. However, there is a lack of physiotherapy tools offers in the market for people with disability (PwD) such as obesity. Therefore, this research aims to understand the portability and flexibility of physiotherapy tools for people with obesity especially in dealing with their job performance. The objective of this study is to identify the physiotherapy tools in the rehabilitation process and to determine the portability and flexibility of the physiotherapy tools for the rehabilitation. Research methods were employed during the process of this study, which includes literature review, product line-up and interviews. From this research, 2 kinds of variables that needs to be consider in the physiotherapy tools which are portability; lightweight, foldable and small in size, and flexibility; easy to be used at any time and offer several kinds of exercises. By considering more on portability and flexibility of the physiotherapy tools for the rehabilitation can help the patient with obesity to conduct selfrehab at their preferred places; working place and homes thus boosting their healthy lifestyle. Based on the findings of this study, a new physiotherapy tools is recommended to provide an excellent portability and flexibility of the physiotherapy tools for obese patients.